A method for preparing a fast-charging silicon oxide negative electrode
By using LixPAA as the binder in the silicon oxide negative electrode material and spray-drying treatment, a stable SEI layer and conductive network are formed, which solves the problem of large volume changes in the charge and discharge cycle of silicon oxide negative electrode material, and significantly improves its rate performance and cycle stability.
Patent Information
- Application Number
- CN202411060191.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-05
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-08-05
AI Technical Summary
The existing silicon oxide negative electrode materials have large volume changes during the charge and discharge cycle, resulting in unstable electrode structure, affecting its rate performance and cycle life.
LixPAA is used as the binder for the spray drying process. By mixing with sub-silicon oxide powder and spray drying, a stable SEI layer and conductive network are formed, buffering volume changes, and the interface stability of the electrode and electron/ion transmission efficiency are improved.
It significantly improves the rate performance and cycle stability of the silicon oxide negative electrode material, solves problems such as large volume expansion rate and high capacity attenuation rate, and has a mild process and is easy to industrialize.
Smart Images

Figure CN118970050B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a fast-charging silicon iodide negative electrode, belonging to the technical field of negative electrode materials for lithium-ion batteries, and is particularly useful for new energy vehicle batteries. Background Art
[0002] With the development of science and technology and society, the sales of new energy vehicles have exploded exponentially. As an extremely important part of the power system of new energy vehicles, lithium-ion batteries require higher energy density, lower cost and faster charging speed to meet the needs of the battery technology industry. The traditional graphite negative electrode materials on the market are obviously unable to meet the needs of the rapidly developing industry. Therefore, it is urgent to find a fast-charging battery negative electrode material with better rate performance and better cycle stability.
[0003] Compared with traditional graphite negative electrode materials, silicon oxide negative electrode materials have a higher theoretical specific capacity, with a theoretical specific capacity of up to 2600mAh / g. They also have the advantages of wide distribution of raw materials and suitable discharge platform. However, the poor electronic conductivity and ionic conductivity of silicon oxide materials greatly affect the performance of their electrochemical performance. At the same time, silicon oxide materials have a larger volume than traditional graphite materials, which is not conducive to lightweight and thin battery design. Silicon oxide materials will be damaged during the charge and discharge cycle, resulting in a shortened life and affecting their cycle performance. Therefore, how to further alleviate its volume change and maintain the stability of the electrode structure is still a key technical issue for the material to become practical. Of course, the electrochemical performance of silicon oxide materials can be improved through modification. The current mainstream methods include surface coating, nano-sizing, structural design, pre-lithiation, etc.
[0004] Chinese patent application CN 114464785A places silicon oxide in a CVD reactor for carbon coating, then stops introducing organic carbon source gas and performs high-temperature disproportionation treatment. This method improves the fast charging capability by means of surface coating, but this method is relatively traditional and has limited improvement in rate performance and cycle performance. Chinese patent application CN 115986094A first pre-lithiates silicon oxide, then mixes silicon oxide with the pre-lithiated silicon oxide core, performs heat treatment under inert atmosphere conditions, obtains a silicon oxide coating layer, and finally coats the surface of the silicon oxide coating layer with an amorphous carbon layer to obtain a pre-lithiated silicon oxide negative electrode material with a core-shell structure. This method effectively improves the various properties of the material, but the method is costly, energy-intensive, and complex in process, which is not conducive to large-scale production.
[0005] The present invention uses Li in the preparation process x PAA as a binder in the spray drying process, Li xPAA can compensate for the loss of lithium ions in a complete lithium-ion battery by acting as an additional lithium source. It has the same properties as PAA, providing carboxyl groups to react with the carboxyl groups on the surface of silicon oxide while also forming a continuous conductive network between particles. x PAA can also form a stable solid electrolyte interface (SEI) layer on the electrode surface, which helps to improve the interface stability of the electrode and the transmission efficiency of electrons / ions. The stable SEI layer can prevent direct contact between the electrolyte and the electrode material, reduce the occurrence of side reactions, and thus extend the cycle life of the battery. x PAA can pre-lithiate silicon oxide, so that silicon oxide generates elemental silicon, lithium oxide and lithium silicate. The elemental silicon generated in situ is dispersed in the lithium oxide-lithium silicate amorphous matrix. Such a structure can buffer the volume change caused by the active silicon deintercalation process. Compared with traditional carbon coating, the use of spray drying to prepare negative electrode materials not only solves the problems of high energy consumption and complex process of carbon coating process, but also increases the specific surface area and pore volume of the material, significantly improves the rate performance of the material, and solves the problems of large volume expansion rate and high capacity attenuation rate of silicon oxide negative electrode materials. The present invention is used to modify the silicon oxide negative electrode material, which effectively improves the rate performance and cycle performance of the silicon oxide negative electrode material. This method is expected to be promoted on a large scale and can affect the future development of lithium-ion batteries. Summary of the invention
[0006] In order to solve the above problems, the purpose of the present invention is to provide a method for preparing a fast-charging silicon oxide negative electrode, solve the problems of poor cycle performance and rate performance of existing lithium batteries, and on the other hand, provide a simple and low-cost method for preparing a fast-charging silicon oxide negative electrode. Finally, a fast-charging silicon oxide-based negative electrode material with excellent step rate performance and good stability is prepared.
[0007] In order to achieve the above purpose, the technical solution adopted in this application is:
[0008] A method for preparing a fast-charging silicon dioxide negative electrode comprises the following steps:
[0009] dissolving PAA and LiOH·H2O in solvents to obtain PAA solution and LiOH solution respectively;
[0010] The PAA solution and LiOH solution were mixed and stirred to obtain Li x PAA binder, where x is 0.25-1;
[0011] Li x Add silicon oxide powder to PAA binder for pre-reaction, then add solvent, and continue stirring to react to obtain a mixed solution;
[0012] The mixed solution is spray-dried to obtain a fast-charging silicon iodide negative electrode.
[0013] The PAA has an average molecular weight of 10W-25W.
[0014] The solid content of the PAA solution is 5wt% to 25wt%; the solid content of the LiOH solution is 5wt% to 20wt%.
[0015] The mass ratio of PAA to LiOH·H2O is (1-7):1.
[0016] The Li x The solid content of PAA binder is 5wt% to 25wt%, and the silicon oxide powder and Li x The mass ratio of PAA binder is (3-10):1.
[0017] The solvent is deionized water, ethanol or tetrahydrofuran.
[0018] The pre-reaction is carried out for 10 to 60 minutes; the stirring reaction is continued at a stirring speed of 200-1000 r / min, the reaction is carried out for 12 to 24 hours, and finally ultrasonically treated at an ultrasonic frequency of 30 to 120 KHz for 20 to 60 minutes to obtain a mixed solution.
[0019] The spray drying atmosphere is one or any combination of air, argon, nitrogen and helium.
[0020] The spray drying air inlet temperature is 200-240°C, and the air outlet temperature is 90-100°C.
[0021] The PAA solution, LiOH solution and SiO x The mixed solution is directly mixed to obtain a mixed solution, wherein 0<x<2, and the mixed solution is spray-dried to obtain a fast-charging silicon iodide negative electrode.
[0022] The beneficial effects of the present invention are:
[0023] 1. This method uses a lithiated binder for spray drying to prepare a lithium-ion battery negative electrode material. x PAA binder, Li x PAA can compensate for the loss of lithium ions in a complete lithium-ion battery by acting as an additional lithium source. It has the same properties as PAA, providing carboxyl groups to react with carboxyl groups on the surface of silicon oxide while also forming a continuous conductive network between particles. x As an elastic binder, PAA can adapt to this volume change to a certain extent, maintain the structural integrity of the electrode, and reduce damage caused by mechanical stress. xPAA can also form a stable SEI layer on the electrode surface, which helps to improve the interface stability of the electrode and the transmission efficiency of electrons / ions. The stable SEI layer can prevent direct contact between the electrolyte and the electrode material, reduce the occurrence of side reactions, and thus extend the cycle life of the battery. x PAA can pre-lithiate silicon oxide, converting silicon oxide into elemental silicon, lithium oxide, and lithium silicate. The in-situ generated elemental silicon is dispersed in the lithium oxide-lithium silicate amorphous matrix. This structure can buffer the volume change caused by the lithium extraction process of active silicon. x PAA, as a binder in the spray drying process, generates lithium silicate in advance, buffering the volume change caused by the active silicon deintercalation and lithium insertion process; at the same time, it generates a stable SEI layer, which improves the interface stability of the electrode and the transmission efficiency of electrons / ions. Spray drying technology is used to convert liquids or solutions into dry solid powders to produce silicon oxide spherical particles, which can solve the problems of large volume expansion rate and high capacity attenuation rate of silicon oxide negative electrode materials. The lithium binder is introduced into the spray drying technology to prepare high-performance fast-charge lithium-ion battery negative electrode materials.
[0024] 2. PAA binder and Li x PAA binders contain a large number of carboxyl (-COOH) groups, which form hydrogen bonds with the hydroxyl (-OH) functional groups on the silicon surface, thereby improving adhesion and being more conducive to the bonding of silicon dioxide during the spray drying process. x PAA can pre-lithiate silicon oxide, converting silicon oxide into elemental silicon, lithium oxide, and lithium silicate. The in-situ generated elemental silicon is dispersed in the lithium oxide-lithium silicate amorphous matrix. This structure can buffer the volume change caused by the active silicon deintercalation and lithium insertion process. x PAA can also form a stable SEI layer on the electrode surface, which helps to improve the interface stability of the electrode and the transmission efficiency of electrons / ions.
[0025] 3. Currently, the methods for preparing fast-charging silicon oxide materials are relatively simple, mainly carbon coating the silicon oxide materials. The present invention combines silicon oxide with a lithium binder and performs a spray drying process. A fast-charging silicon oxide-based negative electrode material with excellent step rate performance and good stability is prepared. This method is expected to be used on a large scale and promote the development of the industry.
[0026] 4. Currently, silicon dioxide anodes require high-temperature heat treatment methods exceeding 200°C, while the present invention can prepare Li x PAA binder, silica powder and Li xThe PAA binder is pre-reacted first, and then the solvent is added to continue the reaction, all at room temperature, and finally the fast-filling silicon oxide material can be prepared by spray drying, without any high-temperature heat treatment method exceeding 200°C. The fast-filling silicon oxide material can be prepared by room temperature and spray drying, the reaction conditions are mild, and it is easier to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a SEM image of the negative electrode material obtained in Example 2;
[0028] Figure 2 This is a SEM image of the negative electrode material obtained in Example 3;
[0029] Figure 3 This is the SEM image of the negative electrode material obtained in Comparative Example 2;
[0030] Figure 4 This is a step rate performance diagram of the negative electrode material obtained in Example 2. DETAILED DESCRIPTION
[0031] In order to more clearly illustrate the technical solution of the present invention, the present invention will be described in detail in conjunction with the embodiments below. The specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work belong to the scope of protection of the present invention. The raw materials used in the present invention are not indicated by the manufacturer, and are all conventional products that can be purchased commercially.
[0032] The present invention mixes silicon oxide and a lithiated binder and then dries them by spray drying, and granulates them while drying to obtain a compact and stable structure. By using LiPAA as a binder, LiPAA can lithiate silicon oxide in advance, so that silicon oxide generates elemental silicon, lithium oxide and lithium silicate. The elemental silicon generated in situ is dispersed in the lithium oxide-lithium silicate amorphous matrix, and such a structure can buffer the volume change caused by the active silicon deintercalation and lithium insertion process; LiPAA can also form an SEI layer on the electrode surface, which helps to improve the interface stability of the electrode and the transmission efficiency of electrons / ions. The combination of the two methods greatly improves the rate performance and electrochemical stability of the negative electrode material.
[0033] The present invention will be further described below in conjunction with the accompanying drawings and specific implementation methods.
[0034] Example 1
[0035] The method for preparing the fast-charging silicon monoxide negative electrode comprises the following steps:
[0036] S1. Dissolve 1.4 g LiOH·H2O in deionized water to prepare a 5 wt% lithium hydroxide solution;
[0037] 3.2 g PAA was dissolved in deionized water to prepare a 10 wt% PAA solution;
[0038] S2. PAA solution and LiOH solution were mixed and reacted for 12 h with magnetic stirring (stirring speed was 500 r / min) to obtain Li 0.75 PAA binder;
[0039] S3, Li 0.75 Add 16g of silicon oxide powder to the PAA binder, with the mass ratio of silicon oxide to binder being 4:1, and pre-react at room temperature for 30 minutes;
[0040] Then add deionized water as solvent, and continue to stir at room temperature (stirring speed is 600 r / min) for 12 h;
[0041] Ultrasonicate the solution at an ultrasonic frequency of 50 KHz for 30 minutes to uniformly disperse silicon dioxide in the solution to obtain a mixed solution;
[0042] S4. The mixed liquid is spray dried in an air atmosphere with an inlet temperature of 220°C, an outlet temperature of 95°C, and a peristaltic pump speed of 20 r / min to obtain a fast-charging silicon iodide negative electrode.
[0043] Example 2
[0044] The method for preparing the fast-charging silicon monoxide negative electrode comprises the following steps:
[0045] S1. Dissolve 1.16 g LiOH·H2O in deionized water to prepare a 5 wt% lithium hydroxide solution;
[0046] Dissolve 2.67 g PAA in deionized water to prepare a 10 wt% PAA solution;
[0047] S2. PAA solution and LiOH solution were mixed and reacted for 12 h with magnetic stirring (stirring speed was 600 r / min) to obtain Li 0.75 PAA binder;
[0048] S3, Li 0.75 Add 16.6g of silicon oxide powder to the PAA binder, with the mass ratio of silicon oxide to binder being 5:1, and pre-react at room temperature for 40min;
[0049] Then add deionized water as solvent, and continue to stir at room temperature (stirring speed is 700 r / min) for 12 h;
[0050] Ultrasonicate the solution at an ultrasonic frequency of 60 KHz for 30 minutes to uniformly disperse silicon dioxide in the solution to obtain a mixed solution;
[0051] S4. The mixed liquid is spray dried in an air atmosphere with an inlet temperature of 220°C, an outlet temperature of 95°C, and a peristaltic pump speed of 20 r / min to obtain a fast-charging silicon iodide negative electrode.
[0052] The SEM image of the fast-charging silicon dioxide negative electrode prepared in this embodiment is as follows Figure 1 As shown, from Figure 1 It can be seen from the figure that the silicon oxide particles are agglomerated into spheres after spray drying. The silicon oxide after treatment has high sphericity and the particles are tightly bonded. The step rate performance diagram of the fast-charging silicon oxide negative electrode material prepared in this embodiment is shown in FIG. Figure 4 As shown, from Figure 4 It can be seen that according to the relationship between silicon oxide and Li 0.75 The silicon oxide negative electrode material prepared with a PAA binder mass ratio of 5:1 was tested for rate performance after the battery was assembled. Its efficiency was stable and it could still maintain a charge and discharge specific capacity of more than 450mAh / g at 4C.
[0053] Example 3
[0054] The method for preparing the fast-charging silicon monoxide negative electrode comprises the following steps:
[0055] S1. Dissolve 0.64 g LiOH·H2O in deionized water to prepare a 5 wt% lithium hydroxide solution;
[0056] Dissolve 1.45 g PAA in deionized water to prepare a 10 wt% PAA solution;
[0057] S2. PAA solution and LiOH solution were mixed and reacted for 12 h with magnetic stirring (stirring speed was 600 r / min) to obtain Li 0.75 PAA binder;
[0058] S3, Li 0.75 Add 18.2g of silicon oxide powder to the PAA binder, with the mass ratio of silicon oxide to binder being 10:1, and pre-react at room temperature for 35min;
[0059] Then add deionized water as solvent, and continue stirring at room temperature (stirring speed is 600 r / min) for 14 h;
[0060] Ultrasonicate the solution at an ultrasonic frequency of 80 KHz for 20 minutes to uniformly disperse silicon dioxide in the solution to obtain a mixed solution;
[0061] S4. The mixed liquid is spray dried in an air atmosphere with an inlet temperature of 230°C, an outlet temperature of 100°C, and a peristaltic pump speed of 25 r / min to obtain a fast-charging silicon iodide negative electrode.
[0062] The SEM image of the fast-charging silicon dioxide negative electrode prepared in this embodiment is as follows Figure 2 As shown, from Figure 2 It can be seen that the silicon oxide particles are agglomerated into spheres after spray drying, but compared with Example 2, the sphericity of the silicon oxide after treatment in Example 3 is lower and the particles are not tightly bonded.
[0063] Example 4
[0064] The method for preparing the fast-charging silicon monoxide negative electrode comprises the following steps:
[0065] S1, dissolving 0.83 g LiOH·H2O in deionized water to prepare a 5 wt% lithium hydroxide solution;
[0066] Dissolve 2.85 g PAA in deionized water to prepare a 10 wt% PAA solution;
[0067] S2. PAA solution and LiOH solution were mixed and reacted for 10 h with magnetic stirring (stirring speed was 500 r / min) to obtain Li 0.5 PAA binder;
[0068] S3, Li 0.5 Add 16.6g of silicon oxide powder to the PAA binder, with the mass ratio of silicon oxide to binder being 5:1, and pre-react at room temperature for 20 minutes;
[0069] Then add deionized water as solvent, and continue stirring at room temperature (stirring speed is 800 r / min) for 12 h;
[0070] Ultrasonicate the solution at an ultrasonic frequency of 60 KHz for 30 minutes to uniformly disperse silicon dioxide in the solution to obtain a mixed solution;
[0071] S4. The mixed liquid is spray dried in an air atmosphere with an inlet temperature of 220°C, an outlet temperature of 90°C, and a peristaltic pump speed of 30 r / min to obtain a fast-charging silicon dioxide negative electrode.
[0072] Example 5
[0073] The method for preparing the fast-charging silicon monoxide negative electrode comprises the following steps:
[0074] S1, dissolving 0.45 g LiOH·H2O in deionized water to prepare a 5 wt% lithium hydroxide solution;
[0075] 3.08 g PAA was dissolved in deionized water to prepare a 10 wt% PAA solution;
[0076] S2. PAA solution and LiOH solution were mixed and reacted for 12 h with magnetic stirring (stirring speed was 600 r / min) to obtain Li 0.25 PAA binder;
[0077] S3, Li 0.25 Add 16.6g of silicon oxide powder to the PAA binder, with the mass ratio of silicon oxide to binder being 5:1, and pre-react at room temperature for 15 minutes;
[0078] Then add deionized water as solvent, and continue to stir at room temperature (stirring speed is 500r / min) for 12h;
[0079] Ultrasonicate the solution at an ultrasonic frequency of 80 KHz for 30 minutes to uniformly disperse silicon dioxide in the solution to obtain a mixed solution;
[0080] S4. The mixed liquid is spray dried in an air atmosphere with an inlet temperature of 220°C, an outlet temperature of 90°C, and a peristaltic pump speed of 30 r / min to obtain a fast-charging silicon dioxide negative electrode.
[0081] Comparative Example 1
[0082] This comparative example has the same preparation steps as Example 1, except that PAA replaces LiPAA, and specifically includes the following steps:
[0083] S1. Dissolve 3.2 g of PAA in water to prepare a 10 wt % PAA solution, and place the solution in a magnetic stirrer and stir at room temperature for 12 h to obtain a PAA solution.
[0084] S2. Mix 16g of silicon oxide powder and PAA binder, dissolve in ultrapure water, the mass ratio of silicon oxide to binder is 4:1, and pre-react at room temperature for 30min;
[0085] Then add deionized water as solvent, and continue to stir at room temperature (stirring speed is 600 r / min) for 12 h;
[0086] Ultrasonicate the solution at an ultrasonic frequency of 50 KHz for 30 minutes to uniformly disperse silicon dioxide in the solution to obtain a mixed solution;
[0087] S3, after stirring the mixed solution in step S2 evenly, spray drying is performed in an air atmosphere, with an inlet temperature of 220°C, an outlet temperature of 65°C, and a peristaltic pump speed of 20 r / min, to obtain spherical silicon oxide particles. The silicon oxide particles in the barrel are recovered to obtain silicon oxide negative electrode material.
[0088] Comparative Example 2
[0089] This comparative example differs from Example 2 only in that PAA replaces LiPAA, and specifically comprises the following steps:
[0090] S1. Dissolve 2.67 g PAA in water to prepare a 10 wt % PAA solution, and place the solution in a magnetic stirrer and stir at room temperature for 12 h to obtain a PAA solution.
[0091] S2, prepare 16.6g of silicon oxide powder and PAA binder, dissolve in ultrapure water, the mass ratio of silicon oxide to binder is 5:1, pre-react at room temperature for 40min;
[0092] Then add deionized water as solvent, and continue to stir at room temperature (stirring speed is 700 r / min) for 12 h;
[0093] Ultrasonicate the solution at an ultrasonic frequency of 60 KHz for 30 minutes to uniformly disperse silicon dioxide in the solution to obtain a mixed solution;
[0094] S3, after stirring the mixed solution in step S2 evenly, spray drying is performed in an air atmosphere, with an inlet temperature of 220°C, an outlet temperature of 95°C, and a peristaltic pump speed of 20 r / min, to obtain spherical silicon oxide particles. The silicon oxide particles in the barrel are recovered to obtain silicon oxide negative electrode material.
[0095] The SEM image of the fast-charging silicon oxide negative electrode prepared in Comparative Example 2 is as follows Figure 3 As shown, Figure 3 In Example 2 Figure 1 By comparison, we can find Figure 3 The sphericity of silicon oxide in the material is poor, the spherical radius is small, and the bonding effect is poor.
[0096] Comparative Example 3
[0097] This comparative example differs from Example 3 only in that PAA replaces LiPAA, and specifically comprises the following steps:
[0098] S1. Dissolve 1.45 g of PAA in water to prepare a 10 wt % PAA solution, and place the solution in a magnetic stirrer and stir at room temperature for 12 h to obtain a PAA solution.
[0099] S2, prepare 18.2g of silicon oxide powder and PAA binder, dissolve in ultrapure water, the mass ratio of silicon oxide to binder is 10:1, pre-react at room temperature for 35min;
[0100] Then add deionized water as solvent, and continue to stir at room temperature (stirring speed is 700 r / min) for 14 h;
[0101] Ultrasonicate the solution at an ultrasonic frequency of 80 KHz for 20 minutes to uniformly disperse silicon dioxide in the solution to obtain a mixed solution;
[0102] S3, after stirring the mixed solution in step S2 evenly, spray drying is performed in an air atmosphere, with an inlet temperature of 230°C, an outlet temperature of 100°C, and a peristaltic pump speed of 25 r / min, to obtain spherical silicon oxide particles. The silicon oxide particles in the barrel are recovered to obtain silicon oxide negative electrode material.
[0103] Comparative Example 4
[0104] This comparative example is different from Example 1 in that there is no pre-reaction and ultrasonic dispersion in S3, and specifically comprises the following steps:
[0105] The method for preparing the fast-charging silicon monoxide negative electrode comprises the following steps:
[0106] S1. Dissolve 1.4 g LiOH·H2O in deionized water to prepare a 5 wt% lithium hydroxide solution;
[0107] Dissolve 3.2 g PAA in deionized water to prepare a 10 wt% PAA solution.
[0108] S2. PAA solution and LiOH solution were mixed and reacted for 12 h with magnetic stirring (stirring speed was 500 r / min) to obtain Li 0.75 PAA binder;
[0109] S3, Li 0.75 16 g of silicon oxide powder was added to the PAA binder, with the mass ratio of silicon oxide to binder being 4:1, and then deionized water was added as a solvent, and the mixture was stirred at room temperature (stirring speed was 600 r / min) for 12 h to obtain a mixed solution;
[0110] S4. The mixed liquid is spray dried in an air atmosphere with an inlet temperature of 220°C, an outlet temperature of 95°C, and a peristaltic pump speed of 20 r / min to obtain a fast-charging silicon iodide negative electrode.
[0111] Test method:
[0112] The above examples and comparative examples were electrochemically tested according to the following method:
[0113] Weigh the negative electrode material and conductive carbon black Super according to the mass ratio of 70:15:5:10. P, CMC and SBR, a small amount of water is added during the mechanical mixing process until the mixture becomes viscous and gelatinous, and then it is evenly coated on the surface of the current collector copper foil by an automatic coating machine, and then placed in a vacuum drying oven at 60°C for drying, and then cut into circular pole pieces with a diameter of 14 mm and placed in an argon glove box for standby; button batteries are assembled in the order of negative electrode shell, silicon oxygen negative electrode, electrolyte, diaphragm, electrolyte, positive electrode lithium sheet, gasket, shrapnel, and positive electrode shell. After standing at room temperature for 2 hours, they are discharged at a constant current of 150mAh / g to 0.01V, then at a constant current of 75mAh / g to 0.01V, and then at a constant current of 20mAh / g to 0.001V, and then at a constant current of 150mAh / g to 1.5V to complete activation, and after activation, the lithium-ion battery data of silicon oxygen with high stable cycle performance is obtained by constant current charge and discharge test at 300mAh / g.
[0114] The assembled battery part of the rate test is the same as the cycle test. The test method is to rest at room temperature for 2 hours, and then cycle 5 times at 0.1C, 0.2C, 0.5C, 1C, 2C, and 4C respectively, and finally obtain the silicon-oxygen high-rate performance lithium-ion battery data.
[0115] Table 1: Rate discharge performance test results
[0116]
[0117]
[0118] After comparison, it was found that the negative electrode material prepared by adding LiPAA had better rate performance and cycle stability than the negative electrode material prepared by adding PAA. x The battery performance of the negative electrode material prepared by PAA, and finally concluded that when x = 0.75, the battery rate performance and cycle stability are the best. The effects of different ratios of silicon oxide and LiPAA binder on battery performance were also compared, and it was finally inferred that when the mass ratio of silicon oxide to binder is 5:1, the battery rate performance and cycle stability are the best. The analysis of the data shows that the silicon oxide negative electrode material for fast-charge lithium-ion batteries prepared by spray drying with the addition of a lithiated binder has good electrochemical properties and has good application prospects and value.
[0119] The products invented and produced basically meet the market demand for power batteries. Compared with existing negative electrode products on the market, they have the advantages of excellent cycle performance, low cost and low price.
[0120] The embodiments and comparative examples described above are only preferred embodiments of the present invention and are only used to explain the present invention, not to limit the scope of implementation of the present invention. For those skilled in the art, other implementation methods can certainly be easily made by replacement or modification based on the technical contents disclosed in this specification. Therefore, all changes and improvements made to the principles and process conditions of the present invention should be included in the scope of the patent application of the present invention.
[0121] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, they are also intended to be included.
Claims
1. A method for preparing a fast-charging silicon oxide negative electrode material, characterized in that: The following steps are involved: dissolving PAA and LiOH·H2O in solvents respectively to obtain PAA solution and LiOH·H2O solution; The PAA solution and LiOH·H2O solution were mixed and stirred to obtain Li x PAA binder, where x is 0.25-1; Li x Add silicon oxide powder to PAA binder for pre-reaction, then add solvent, and continue stirring to react to obtain a mixed solution; The mixed solution is spray-dried to obtain a fast-charging silicon oxide negative electrode material; The pre-reaction time is 10 to 60 minutes; the stirring speed of the stirring reaction is continued at 200-1000 r / min, the reaction is carried out for 12 to 24 hours, and finally the ultrasonic frequency is 30 to 120 KHz for 20 to 60 minutes to obtain a mixed solution; Silicon oxide powder and the Li x The mass ratio of PAA binder is (3-10):1; Li x PAA binder lithiates silicon oxide powder, converting silicon oxide into elemental silicon, lithium oxide and lithium silicate.
2. The method for preparing the fast-charging silicon 2 oxide negative electrode material according to claim 1, characterized in that: The average molecular weight of the PAA is 10W to 25W.
3. The method for preparing the fast-charging silicon 2 oxide negative electrode material according to claim 1, characterized in that: The solid content of the LiOH·H2O solution is 5wt% to 20wt%.
4. The method for preparing the fast-charging silicon 2 oxide negative electrode material according to claim 1, characterized in that: The mass ratio of PAA to LiOH·H2O is (1-7):
1.
5. The method for preparing the fast-charging silicon 2 oxide negative electrode material according to claim 1, characterized in that: The Li x The solid content of the PAA binder is 5 wt % to 25 wt %.
6. The method for preparing the fast-charging silicon 2 oxide negative electrode material according to claim 1, characterized in that: The solvent is deionized water, ethanol or tetrahydrofuran.
7. The method for preparing the fast-charging silicon 2 oxide negative electrode material according to claim 1, characterized in that: The spray drying atmosphere is one or any combination of air, argon, nitrogen and helium.
8. The method for preparing the fast-charging silicon 2 oxide negative electrode material according to claim 1, characterized in that: The spray drying air inlet temperature is 200-240°C, and the air outlet temperature is 90-100°C.
Citation Information
Patent Citations
Carbon-coated silicon monoxide negative electrode material, preparation method thereof and lithium ion battery
CN114464785A
Pre-lithiated silicon monoxide negative electrode material with core-shell structure as well as preparation method and application of pre-lithiated silicon monoxide negative electrode material
CN115986094A
Pre-lithiation binder for silicon-carbon power battery and preparation method of silicon-carbon electrode
CN117165227A
Method for preparing negative electrode material by adopting spray drying process
CN117996062A